Direct Quantification of Ligand‐Induced Lipid and Protein Microdomains with Distinctive Signaling Properties. Issue 5 (18th May 2022) - Wirth, Daniel; Paul, Michael D.; Pasquale, Elena B.; Hristova, Kalina
Abstract: Lipid rafts are ordered lipid domains that are enriched in saturated lipids, such as the ganglioside GM1. While lipid rafts are believed to exist in cells and to serve as signaling platforms through their enrichment in signaling components, they have not been directly observed in the plasma membrane without treatments that artificially cluster GM1 into large lattices. Here, we report that microscopic GM1‐enriched domains can form in the plasma membrane of live mammalian cells expressing the EphA2 receptor tyrosine kinase in response to its ligand ephrinA1‐Fc. The GM1‐enriched microdomains form concomitantly with EphA2‐enriched microdomains. To gain insight into how plasma membrane heterogeneity controls signaling, we quantify the degree of EphA2 segregation and study initial EphA2 signaling steps in both EphA2‐enriched and EphA2‐depleted domains. By measuring dissociation constants, we demonstrate that the propensity of EphA2 to oligomerize is similar in EphA2‐enriched and ‐depleted domains. However, surprisingly, EphA2 interacts preferentially with its downstream effector SRC in EphA2‐depleted domains. The ability to induce microscopic GM1‐enriched domains in live cells using a ligand for a transmembrane receptor will give us unprecedented opportunities to study the biophysical chemistry of lipid rafts. Abstract : Microscopic GM1‐enriched domains can form in the plasma membrane of live mammalian cells expressing the EphA2 receptor tyrosine kinase in response to its ligand ephrinA1‐Fc. The GM1‐enriched microdomains form concomitantly with EphA2‐enriched microdomains. The propensity of EphA2 to oligomerize is the same in EphA2‐enriched and ‐depleted domains. However, EphA2 interacts preferentially with its downstream effector SRC in EphA2‐depleted domains. This study opens new avenues for investigations of a variety of plasma membrane signaling platforms and the biophysical chemistry of lipid rafts.